Myxospora poaceicola sp. nov. (Stachybotryaceae, Hypocreales), a novel myrothecium-like fungus from Digitaria sanguinalis (Poaceae) - Chen, Yanpeng; Lu, Zhenghua; Faraj, Turki Kh.; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2023)
Fungi belonging to the family Stachybotryaceae play crucial roles in ecosystem dynamics, particularly in decomposing plant materials and pathogens on plants and animals. In this study, we report the isolation of two hitherto unknown hyphomycetous and myrothecium-like fungi collected from two different Poaceae plants in Sichuan Province, China. Molecular analysis based on ITS, LSU, TEF1, RPB2, TUB2, and CAL sequences of newly isolated strains revealed that they represent a previously undescribed species within the genus Myxospora. Phylogenetic investigations employing both maximum-likelihood (ML), maximum parsimony (MP) and Bayesian inference (BI) methods indicated that the new species forms a sister clade with M. masonii and M. graminicola. Nevertheless, M. poaceicola is distinct from these closely related species within the genus by having longer synnemata and wider conidia. We formally designate it as Myxospora poaceicola sp. nov. With the addition of M. poaceicola, the genus Myxospora now comprises six species. This discovery sheds light on the diversity of Myxospora fungi and underscores the importance of further taxonomic exploration in this genus.